Di-Arginine signals and the K-Rich domain retain the Ca2+ sensor STIM1 in the endoplasmic reticulum - Ercan, Ebru; Chung, Shan-Hua; Bhardwaj, Rajesh; Seedorf, Matthias (Traffic, 2012)
Abstract: STIM1 is a core component of the store-operated Ca2+-entry channel involved in Ca2+-signaling with an important role in the activation of immune cells and many other cell types. In response to cell activation, STIM1 protein senses low Ca2+ concentration in the lumen of the endoplasmic reticulum (ER) and activates the channel protein Orai1 in the plasma membrane by direct physical contact. The related protein STIM2 functions similar but its physiological role is less well defined. We found that STIM2, but not STIM1, contains a di-lysine ER-retention signal. This restricts the function of STIM2 as Ca2+ sensor to the ER while STIM1 can reach the plasma membrane. The intracellular distribution of STIM1 is regulated in a cell-cycle-dependent manner with cell surface expression of STIM1 during mitosis. Efficient retention of STIM1 in the ER during interphase depends on its lysine-rich domain and a di-arginine ER retention signal. Store-operated Ca2+-entry enhanced ER retention, suggesting that trafficking of STIM1 is regulated and this regulation contributes to STIM1s role as multifunctional component in Ca2+-signaling.